Code Red [large type] - Mills, Kyle, 1966-; Flynn, Vince, 1966-2013 (Flynn, Vince, 1966-2013. Mitch Rapp novel, 2023)
"Mitch Rapp hates owing anyone a favor - especially when it's the world's most powerful crime lord. But when Damian Losa calls, Mitch is honor-bound to answer. The Syrian government appears to have created a highly addictive new narcotic that it plans to distribute throughout Europe. It's a major threat to Losa's business and he's determined to send someone to keep him on top by any means necessary. Rapp is the perfect choice for the mission. Not only does he have extensive experience operating in the Middle East, but he's also entirely expendable. As he crosses into war-torn Syria, Rapp quickly discovers a shocking truth. The new drug isn't being produced by Damascus to prop up the government's collapsing finances. Instead, it was created by Russia's asymmetrical warfare unit, not for profit but as a weapon against the West. With far more than Damian Losa's interests at stake, Rapp devises a desperate plan that forces him and his team onto a battlefield where the United States is virtually powerless and allegiances shift almost hourly. Further, if Russia uncovers their plot, it will set off a confrontation between the two countries that could change the course of human history."--